2003
DOI: 10.1074/jbc.m308956200
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Stoichiometry of Interaction of DnaG Primase with DnaB Helicase of Escherichia coli in RNA Primer Synthesis

Abstract: Initiation and synthesis of RNA primers in the lagging strand of the replication fork in Escherichia coli requires the replicative DnaB helicase and the DNA primase, the DnaG gene product. In addition, the physical interaction between these two replication enzymes appears to play a role in the initiation of chromosomal DNA replication. In vitro, DnaB helicase stimulates primase to synthesize primers on single-stranded (ss) oligonucleotide templates. Earlier studies hypothesized that multiple primase molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
75
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 60 publications
5
75
0
2
Order By: Relevance
“…The data suggested that the single DnaB replication fork helicase loaded on the lagging strand could recruit DnaG primase molecules to reprime not only on the lagging strand but also on the leading strand ( Figure 2B). The recent finding that multiple primase monomers can bind a DnaB hexamer [12] supports the idea that a single helicase can mediate the recruitment of more than one DnaG molecule, thus possibly mediating both lagging and leading strand priming events.…”
mentioning
confidence: 56%
“…The data suggested that the single DnaB replication fork helicase loaded on the lagging strand could recruit DnaG primase molecules to reprime not only on the lagging strand but also on the leading strand ( Figure 2B). The recent finding that multiple primase monomers can bind a DnaB hexamer [12] supports the idea that a single helicase can mediate the recruitment of more than one DnaG molecule, thus possibly mediating both lagging and leading strand priming events.…”
mentioning
confidence: 56%
“…Protein titration led to a concentration-dependent quenching of F-ID1, where the total fluorescence of the system is equal to the denominator of Equation 2. Thus, the raw anisotropy data were corrected for quenching using Equation 3, as described previously (63).…”
Section: Determination Of Fementioning
confidence: 99%
“…In vitro experiments with the E. coli DnaB and DnaG proteins showed that DnaB modulates the activity of DnaG in several ways. One role of DnaB is to transport the bound DnaG to its recognition sites (5,7,12). In addition, DnaB also modulates primer synthesis in a manner independent of its translocation ability.…”
mentioning
confidence: 99%